2007
DOI: 10.1007/s00484-007-0093-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sprinkling on feedlot microclimate and cattle behavior

Abstract: Experiments were conducted to evaluate strategies designed to reduce heat stress of cattle. In the first experiment, cattle were sprinkled for 20 min every 1.5 h between 1000 hours and 1750 hours (WET) versus not sprinkled (DRY). In a second experiment, treatments consisted of: (1) control, no water application; (2) water applied to the pen surfaces between 1000 hours and 1200 hours (AM); and (3) water applied to pen surfaces between 1400 hours and 1600 hours (PM). In both experiments, sprinkling lowered (P < … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 25 publications
1
28
0
2
Order By: Relevance
“…Similar dirt temperatures were described previously by Sullivan et al (2011) fig. 3), and hourly variation in ground temperature was similar (18°F [10°C] on dry dirt) to that described by Mader et al (2007). Other studies have shown that cows seek areas with cooler ground temperatures during the warmest part of the day (Mader et al 2007).…”
Section: Grazyne Tresoldisupporting
confidence: 55%
“…Similar dirt temperatures were described previously by Sullivan et al (2011) fig. 3), and hourly variation in ground temperature was similar (18°F [10°C] on dry dirt) to that described by Mader et al (2007). Other studies have shown that cows seek areas with cooler ground temperatures during the warmest part of the day (Mader et al 2007).…”
Section: Grazyne Tresoldisupporting
confidence: 55%
“…Nos ambientes com condições muito estressantes para as vacas leiteiras confinadas, o uso de técnicas de climatização como, por exemplo, sistemas de resfriamento adiabático-evaporativo (SRAE), pode constituir-se em alternativa viável para mitigar o estresse animal por calor (Mader et al, 2007), especialmente para animais com elevados índices de produção. O SRAE permite aumentar o conforto térmico e melhorar a produção e qualidade do leite, principalmente quando dietas adequadas são formuladas para os animais durante os períodos mais quentes.…”
Section: Ações Mitigadoras Dos Efeitos Das Mudanças Climáticas Sobre unclassified
“…Esse índice tem sido bastante utilizado em estudos de avaliação do conforto e/ou desconforto térmico animal (Mader et al, 2007), especialmente em análise de risco climático (Casa e Ravelo, 2003;Pires et al, 2006). Isto se deve ao fato do ITU requerer apenas dados de temperatura e umidade relativa (UR) do ar (Brown-Brandl et al, 2005), diferente de índices como o ITGU (Índice de temperatura do globo negro e umidade), que requer dados de temperatura do globo negro, os quais não são medidos em estações meteorológicas sinóticas.…”
Section: Introductionunclassified